Research advances in rabies - Jackson, Alan C. (Advances in virus research, 2011)
Volume 79 of Advances in Virus Research focuses on developments surrounding rabies, an ancient disease that remains a promiment public health problem for humans. This volume highlights important research advances extending from our understanding of how rabies virus replicates and assembles to how the disease can be prevented and treated in humans and how rabies can be controlled in wildlife hosts. Experts in the fields provide insightful and up-to-date chapters that summarize our current state of knowledge in diverse aspects of this very interesting and important viral disease.